HUBUNGAN KEAKTIFAN LANSIA MENGIKUTI KEGIATAN POSBINDU LANSIA TERHADAP TINGKAT KEMANDIRIAN LANSIA MENGONTROL PENYAKIT HIPERTENSI - Yolanda, Risky Rati; Herlina, Herlina; Safri, Safri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Elderly is someone who has reached the age of 60 (sixty) years and above, the elderly will experience an aging processthat causes an increased risk of high health problems in the elderly, one of the problems of hypertension. efforts toimprove and maintain health can be done by following posbindu elderly on a regular basis. Independence is the abilityor circumstance in which the individual is able to manage or overcome his own interests without being dependent onothers. The liveliness of elderly is activity or busyness of elderly in following posbindu elderly every month in localarea. This study aims to determine the relationship of elderly activity following the posbindu elderly activity toindependence of elderly controlling hypertension disease. This research uses correlation description research designand cross sectional approach. The sample of the research was 76 respondents who were taken based on the inclusioncriteria using Proportionate stratified random sampling technique. The measuring instruments used werequestionnaires and observation sheets. The analysis used is univariate analysis to know the frequency distribution andbivariate using Chi Square. The result showed that 58 respondents were able to control hypertension, 43 respondentswere active in posbindu elderly (84,3%) and 15 respondents were not active in posbindu elderly (15,7%). Based on theresults obtained Chi Square p value 0.04 <a (0.05) and it can be concluded there is a significant relationship betweenthe elderly activeness follow activities posbindu elderly to independence of elderly controlling hypertension disease.The results of this study is expected to elderly to be active in posbindu elderly activities, thus the elderly can controlBlood Pressure.Key words: Activity, Elderly, Hypertension, Independence, Posbindu Elderly